Systematic literature review of Halal purchasing in value chain management. A qualitative research era from 2011 to 2022 - Nurulfaraiza, Ariffin; Veera Pandiyan, Kaliani Sundram; Mohd Hafiz, Zulfakar (Advances in Social Sciences Research Journal, 2023)
In observing the rapid competition among businesses in halal market demand, the globe forces to seek competitive advantages and halal purchasing practice as one of way to improve a company's performance. Over the last decade researchers have studied halal supply chain management from various perspectives in relation to different industries. However, there is limited literature in halal purchasing and value chain since start of twenty-first century. The number of publication papers is still pegged to the lowest ebb. This paper aims to systematically review all qualitative research papers, published in reputed journals on the practices of halal purchasing. This paper will employ a systematic literature review methodology extracted from Scopus database and Google Scholar search engine ranging from 2011 until 2022 totaling 17 articles. The authors review the items of the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) on halal purchasing and value chain have operationalized systematic reviews. The analysis reveals three research clusters: halal purchasing practices, value chain management, and halal supply chain. The findings of this study will help to explore the understanding of halal in purchasing practices and value chain. This study will be useful for researchers and practitioners in their fields as well as to assist the businesses in halal industry and purchasing management.